(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The purpose of this work is to find and develop the optimal shape of the working chamber of the catcher and its working elements, as well as their influence on the fiber yield and the catching effect. For this purpose, an experimental setup was developed and the processes of trapping under-ginned seeds were studied.